Pengaruh Kompentensi dan Kompensasi Terhadap Disiplin Kerja Serta Dampaknya pada Kinerja Karyawan pada PT. BSI KC Arifin Ahmad Pekanbaru - Syafriade Zulmi (Journal of Engineering Science and Technology Management, 2022)
The purpose of this study was to analyze the effect of compensation and competence on work discipline and its impact on employee performance at PT BSI KC Arifin Ahmad Pekanbaru. By using quantitative research methods by conducting a survey of employees of PT BSI KC Arifin Ahmad Pekanbaru. The sample in this study was 82 people. The research method used is a quantitative descriptive approach. The data collection used by the author in this study is a questionnaire. The data collected is primary data. Analysis of the data used is to use path analysis (path analysis). By using software SPSS 17.00 for windows. The results showed that there was a relationship between competence and work discipline, compensation and work discipline. And the effect of competence and compensation on employee performance. And the effect of work discipline on employee performance.